New phenotypes of functional expression of the mKir2.1 channel in potassium efflux-deficient Saccharomyces cerevisiae strains - Koláčná, Lucie; Kinclová-Zimmermannová, Olga; Hasenbrink, G; Schwarzer, S; Ludwig, J; Lichtenberg-Frate, H., H; Sychrová, Hana (Yeast, 2005)
The functional expression of the mouse Kir2.1 potassium channel in yeast cells lacking transport systems for potassium and sodium efflux (ena1-4delta nha1delta) resulted in increased cell sensitivity to high external concentrations of potassium. The phenotype depended on the level of Kir2.1 expression and on the external pH. The activity of Kir2.1p in the yeast cells was almost negligible at pH 3.0 and the highest at pH 7.0. Kir2.1p was permeable for both potassium and rubidium cations, but neither sodium nor lithium were transported via the channel. Measurements of the cation contents in cells confirmed the higher concentration of potassium in cells with Kir2.1p. Specific inhibition of the mKir2.1 channel activity by Ba2+ cations was observed. The use of a mutant strain lacking both potassium efflux and uptake transporters (ena1-4delta nha1delta trk1delta trk2delta) enabled the monitoring of channel activity on two levels--the provision of the necessary amount of intracellular K+ in media with low potassium concentrations, and simultaneously, the channel's contribution to cell potassium sensitivity in the presence of high external K+. This combination of mutations proved to be a new, sensitive and practical tool for characterizing the properties of heterologously expressed transporters mediating both the efflux and influx of alkali-metal-cations. Copyright 2005 John Wiley & Sons, Ltd.
Keywords: Potassium Channels, Inwardly Rectifying; draslík; baryum; transformace genetická; fenotyp; financování organizované; Ion Transport; alkalické kovy; draslíkové kanály dovnitř usměrňující; Metals, Alkali; Saccharomyces cerevisiae; Financing, Organized; Phenotype; Transformation, Genetic; iontový transport; Potassium; Barium